The Effect of biochar on soil chemical properties of tidal wetland in Jambi, Indonesia, and growth and yield of various rice varieties - Panjaitan, Riezky Pratama; Aryunis; Wiskandar, Wiskandar (Journal of Degraded and Mining Lands Management, 2024)
The study aimed to determine the effect of biochar on the growth and yield of several rice varieties in a tidal wetland agroecosystem. This research used a split-plot design with the main plot was biochar application, consisting of three levels (no biochar, rice husk biochar, and coconut shell biochar), and the subplot was rice variety consisting of ten varieties (Inpara, Inpari 30, Kuning, Karya Rendah, Bujang Pelawah, Pandan Wangi, Bujang Berinai, Kwatek Tinggi, Candu, and Serai). Plant parameters observed were plant height, number of tillers, productive tillers, panicle length, number of grains per panicle, number of empty grains per panicle, milled rice weight, and weight of 1,000 grains. Results of this study showed that the application of biochar improved soil fertility by increasing organic carbon, available phosphorus and potassium, cation exchange capacity, and reducing the soluble iron in the soil. However, the application of biochar did not significantly affect the height of rice plants. The application of coconut shell biochar yielded the best results in increasing the number of productive tillers, the number of grains per panicle, grain dry weight, and reducing the number of empty grains per panicle.